The railway information system as a queueing system - Melikyan, Alla (Transport, 2009)
The present article dwells upon the Information System (IS) of Latvian railways providing the analysis of the queuing system (QS) used to removing defects occurring in the infinite linear queuing system. The author of the article analyzes research data about the failures of system functioning in order to establish the parameters of the before mentioned system and other information systems used by Latvian railways. The structure of accidents happening in the informative systems and the removal of possible defects are researched. The present investigation provides evidence that substantiates a Markov hypothesis about the peculiarities of IS service. The author also examines the organizational structure of IS taking into consideration the level of the danger of possible accidents. The statistics of the failures of IS relates to the statistics of accidents that might happen to rolling stock.First published online: 27 Oct 2010